Δύο ἐνεπίγραφα ἐπιτύμβια μνημεῖα ἀπὸ τὴν ἀρχαία Μόρρυλο - Sverkos, Ilias; Savvopoulou, Thomais (Tekmeria, 2018)
Two unpublished inscribed funerary monuments from Ano Apostoloi (ancient Morrylos) dating to the third century A.D. are presented ιn this article: The first has been erected by a wife in memory of her husband, while the second was planned as a tomb both for already deceased family members including a household slave (threpte) and for future burials. The names of the persons mentioned in both inscriptions, for which full commentary is offered, are to be added to those already known from other inscriptions from ancient Morrylos, thus enriching the city’s prosopography.